2012
DOI: 10.1371/journal.pone.0047626
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Lobes Differentiate between the Voices of Famous and Unknown People: An Event-Related fMRI Study on Speaker Recognition

Abstract: It is widely accepted that the perception of human voices is supported by neural structures located along the superior temporal sulci. However, there is an ongoing discussion to what extent the activations found in fMRI studies are evoked by the vocal features themselves or are the result of phonetic processing. To show that the temporal lobes are indeed engaged in voice processing, short utterances spoken by famous and unknown people were presented to healthy young participants whose task it was to identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 90 publications
6
25
0
Order By: Relevance
“…The area of STS we found was most sensitive to the familiar-unfamiliar voice difference is located more posteriorally than the temporal voice areas in some of the previous studies (e.g., 3133). Nevertheless, Bethmann, Scheich, and Brechman (35) found that the greatest difference between familiar and unfamiliar voices occurred in both anterior and posterior areas that were more distant from primary auditory cortex, which is consistent with our results. In addition, Warren et al (36) proposed that abstraction of voice identity information occurs in posterior STS, and subsequent analysis occurs in anterior parts of STS and MTG.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The area of STS we found was most sensitive to the familiar-unfamiliar voice difference is located more posteriorally than the temporal voice areas in some of the previous studies (e.g., 3133). Nevertheless, Bethmann, Scheich, and Brechman (35) found that the greatest difference between familiar and unfamiliar voices occurred in both anterior and posterior areas that were more distant from primary auditory cortex, which is consistent with our results. In addition, Warren et al (36) proposed that abstraction of voice identity information occurs in posterior STS, and subsequent analysis occurs in anterior parts of STS and MTG.…”
Section: Discussionsupporting
confidence: 92%
“…Birkett et al (37) found greater activity for familiar than unfamiliar voices in the left MTG. However, all of these studies either used tasks that asked participants to judge voice familiarity (35, 37) or had participants passively listen to stimuli while speaker identity varied across conditions (36)—whereas the task in the current study was to report the words that were spoken.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators noting normal activation of the fusiform face area in developmental prosopagnosia (Avidan et al, 2005; Avidan et al, 2009) have performed morphometric studies reporting abnormalities in anterior fusiform cortex and the anterior and middle temporal lobes (Behrmann et al, 2007). Functional neuroimaging has revealed temporal voice areas in the middle and anterior superior temporal sulcus, more so on the right (Belin et al, 2000), which show sensitivity to voice identity in adaptation studies (Belin et al, 2003; Warren et al, 2006) and activity correlations with the familiarity of voices (Bethmann et al, 2012). It must be noted, though, that the anterior temporal regions responding to facial identity are more ventral than temporal voice areas (Belin et al, 2000) and do not overlap (Joassin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There are some neuroscience studies on voice recognition (e.g., [3], [6], [7], [20]). Belin et al [6] studied the brain areas involved in voice recognition.…”
Section: B Related Workmentioning
confidence: 99%